Annexin A5 regulates surface αvβ5 integrin for retinal clearance phagocytosis - Yu, Chen; Munoz Becerra, Luis; Mallavarapu, Mallika; Herrmann, Martin; Finnemann, Silvia C. (Journal of cell science, 2019)
Diurnal clearance phagocytosis by the retinal pigment epithelium (RPE) is a conserved efferocytosis process whose binding step is mediated by αvβ5 integrin receptors. Two related annexins, A5 (ANXA5) and A6 (ANXA6), share an αvβ5 integrin-binding motif. Here, we report that ANXA5, but not ANXA6, regulates the binding capacity for spent photoreceptor outer segment fragments or apoptotic cells by fibroblasts and RPE. Similar to αvβ5-deficient RPE, ANXA5-/- RPE in vivo lacks the diurnal burst of phagocytosis that follows photoreceptor shedding in wild-type retina. Increasing ANXA5 in cells lacking αvβ5 or increasing αvβ5 in cells lacking ANXA5 does not affect particle binding. Association of cytosolic ANXA5 and αvβ5 integrin in RPE in culture and in vivo further supports their functional interdependence. Silencing ANXA5 is sufficient to reduce levels of αvβ5 receptors at the apical phagocytic surface of RPE cells. The effect of ANXA5 on surface αvβ5 and on particle binding requires the C-terminal ANXA5 annexin repeat but not its unique N-terminus. These results identify a novel role for ANXA5 specifically in the recognition and binding step of clearance phagocytosis, which is essential to retinal physiology.This article has an associated First Person interview with the first author of the paper.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Annexin A5; Clearance phagocytosis; Efferocytosis; Integrin; Retina; RPE